2020
DOI: 10.1111/1475-6773.13266
|View full text |Cite
|
Sign up to set email alerts
|

Association between state Medicaid expansion status and naloxone prescription dispensing

Abstract: Objective To test whether Medicaid expansion is associated with (a) a greater number of naloxone prescriptions dispensed and (b) a higher proportion of naloxone prescriptions paid by Medicaid. Data Sources/Study Setting We used the IQVIA National Prescription Audit to obtain data on per state per quarter naloxone prescription dispensing for the period 2011‐16. Study Design In this quasi‐experimental design study, the impact of Medicaid expansion on naloxone prescription dispensing was examined using difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
0
14
2
Order By: Relevance
“…Increasing access to buprenorphine through emergency medical services (EMS) personnel ( Davis et al, 2021 ) and clinical pharmacists ( Peckham et al, 2021 ) may be a critical step to ensure widespread access for those in need. Policies that support Naloxone access (e.g., standing orders, health plan coverage) reduce the risk of overdose mortality ( Sohn et al, 2020 , Sohn et al, 2019 ), yet are inconsistently implemented across the United States. Residents of Medicaid expansion states have historically benefited from improved access to Naloxone ( Sohn et al, 2020 ), but it is unknown if these trends persisted during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing access to buprenorphine through emergency medical services (EMS) personnel ( Davis et al, 2021 ) and clinical pharmacists ( Peckham et al, 2021 ) may be a critical step to ensure widespread access for those in need. Policies that support Naloxone access (e.g., standing orders, health plan coverage) reduce the risk of overdose mortality ( Sohn et al, 2020 , Sohn et al, 2019 ), yet are inconsistently implemented across the United States. Residents of Medicaid expansion states have historically benefited from improved access to Naloxone ( Sohn et al, 2020 ), but it is unknown if these trends persisted during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Policies that support Naloxone access (e.g., standing orders, health plan coverage) reduce the risk of overdose mortality ( Sohn et al, 2020 , Sohn et al, 2019 ), yet are inconsistently implemented across the United States. Residents of Medicaid expansion states have historically benefited from improved access to Naloxone ( Sohn et al, 2020 ), but it is unknown if these trends persisted during the COVID-19 pandemic. In light of rising rates of fatal opioid overdose, states should consider implementing Naloxone leave-behind laws that allow EMS personnel to distribute Naloxone after an overdose event to bystanders ( Scharf et al, 2021 , Wood et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Access to health insurance and payor reimbursement also play a role in naloxone distribution. Reimbursement and insurance coverage for naloxone have been increasing among public and private payors ( Sohn et al, 2020 ). However, the price of naloxone without insurance remains high and insurance may only partially cover the expense ( Peet et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 13 States without Medicaid expansion have been found to have lower rates of naloxone dispensation. 5 , 6 Laws that offer different levels of prescriber and dispenser civil and criminal immunity for the consequences of naloxone distribution may also influence dispensation. 14 One more factor contributing to low naloxone use might be the cost of naloxone, with average copays (out of pocket costs for patients to fill a prescription) nearing $25.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that an increase in distribution of naloxone has been linked with reductions in overdose mortality. [2][3][4] Naloxone access has increased in recent years through Medicaid expansion 5,6 and numerous other strategies. 7 At the start of data collection for this study, all states except for Nebraska had an active standing order for naloxone, meaning that a patient or caregiver could obtain the medication without an individual prescription.…”
Section: Introductionmentioning
confidence: 99%